Terapia fotodinâmica antimicrobiana com azul de metileno em solução hidroalcoólica sobre a defesa leucocitária e inflamação sistêmica de ratos diabéticos com periodontite - Custodio, Martina Zanon (2022)
Periodontitis is an inflammatory, chronic and multifactorial disease that develops due to dysbiosis between the dental biofilm and the host's immune response, leading to a progressive destruction of dental attachment and support tissues. Initially, the inflammatory response is a local reaction that activates the innate immune system, stimulating the action of various types of pro-inflammatory cells, as well as tissue resident cells. The amplification of this initially localized response results in the release of a series of cytokines and other mediators and the spread of inflammation. Critical serum concentrations of pro-inflammatory cytokines influence leukocyte cells at the site of injury, playing a key role in the inflammatory process and, consequently, in the bone loss that occurs with the progression of periodontal disease. This study evaluated the adjunctive antimicrobial photodynamic therapy (aPDT) influence effects using methylene blue (MB) solubilized in ethanol on leukocyte defense and systemic inflammation of normoglycemic and diabetic rats with periodontitis. Rats were divided into two main groups: normoglycemics (n=25) and diabetics (n=25). After 14 days of the diabetes induction, each of the groups was subdivided into 5 (n=5), yielding 10 experimental groups, according to periodontal treatment in: negative control (NC; no periodontitis), positive control (PC; periodontitis; without any treatment); scaling and root planning (SRP; periodontitis); SRP plus aPDT with MB dissolved in water (aPDT I; periodontitis); and SRP plus aPDT with MB dissolved in ethanol (aPDT II; periodontitis). The ligature was removed from all animals after 7 days of its placement and periodontal treatments were performed. Seven days after periodontal treatments, the blood was collected for leukocyte and inflammatory profiles analysis. PC group showed higher leukocytes count and cytokines levels. aPDT indicated a protective influence observed by the decreased systemic inflammatory mediators. The aPDT as an adjunct to the SRP can induce the systemic protective response against inflammation periodontitis-induced, particularly when the MB is dissolved in hydroalcoholic solution and in the presence of diabetes.